Characterizations of ceramic insulation coatings on stainless-steel tapes for magnet technology - Çakıroğlu, Ömer; Arda, Lütfi; Aktaş, Şahin (Marmara Üniversitesi Fen Bilimleri Dergisi, 2009)
Characterizations of high temperature ceramic insulation coatings were investigated by surface conductivity, electric strength, dielectric constant, mass lost and corrosion techniques. MgO-ZrO2 was coated on Stainless-Steel-304 (SS) tapes by reel-to-reel sol-gel process for investigation of characterizations of MgO-ZrO2 as insulation coatings. Tapes were produced several dips for application of HTS/LTS high field insert coils and magnets. Solutions were prepared by using Mg and Zr based precursors, solvent and chelating agent, then the insulations was coated on long-length SS substrate. Characterizations of electrical strength and dielectric constant were tested by using standardization equipment. Thermogravimetric (TGA) analyzes in air and in nitrogen was done. The effect of corrosion test according to the standardization of ASTM B 117 was studied. Surface morphology of micrographs of corrosion test samples was examined using ESEM.
Characterizations of ceramic insulation coatings on stainless-steel tapes for magnet technology
Keywords: Electrical properties; dielectric constant; TGA analyzes; corrosion resistance; MgO-ZrO2